2014
DOI: 10.1097/jto.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and the Prognostic Characteristics of Lung Adenocarcinoma Patients with ROS1 Fusion in Comparison with Other Driver Mutations in East Asian Populations

Abstract: The ROS1 fusion gene can be successfully detected in East Asian patients with lung adenocarcinoma using multiplex reverse transcription-polymerase chain reaction. These patients tend to be younger and have characteristic histologic subtypes. Due to the small number of ROS1 fusion patients, the prognostic value of ROS1 fusion need further studies to confirm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
79
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(97 citation statements)
references
References 38 publications
(83 reference statements)
12
79
4
2
Order By: Relevance
“…KRAS mutation is the major genetic alteration in lung adenocarcinoma of Western countries (37). In contrast, KRAS mutation appears to negatively affect overall survival (38,39). However, our study is also limited to identify the potential long-term survival impact of ALK, ROS1, KRAS and other oncogenic mutations.…”
Section: Discussionmentioning
confidence: 93%
“…KRAS mutation is the major genetic alteration in lung adenocarcinoma of Western countries (37). In contrast, KRAS mutation appears to negatively affect overall survival (38,39). However, our study is also limited to identify the potential long-term survival impact of ALK, ROS1, KRAS and other oncogenic mutations.…”
Section: Discussionmentioning
confidence: 93%
“…The strength of evidence supporting the use of any clinical characteristic to identify patients who should receive ROS1 testing was adequate. This recommendation is evidence based and supported by 9 studies, 30e38 6 of which informed on the association between ROS1 rearrangement and patient or tumor characteristics 30,31,34e37 and consisted of 1 prospective cohort study (PCS), 35 1 prospective-retrospective cohort study (PRCS), 31 and 4 retrospective cohort studies (RCSs). 30,34,36,37 The 3 remaining studies assessed clinical outcomes of patients treated with the ROS1-targeted therapy crizotinib 32,33,38 and included 1 nonrandomized clinical trial 33 and 3 RCSs.…”
Section: Strong Recommendationmentioning
confidence: 99%
“…Although relatively rare, accounting for <2% of nonesmall cell lung carcinomas 30,31,34 and 2% to 3% of lung adenocarcinomas, 30,34,35 structural rearrangements involving the ROS1 gene generate an oncogenic fusion that can be treated successfully with targeted inhibitors. A single phase I clinical trial of 50 NSCLC patients demonstrated that the presence of a ROS1 rearrangement by FISH or RT-PCR predicts response to targeted inhibition using crizotinib, with a response rate of 72% and median progression-free survival of 19.2 months.…”
Section: Strong Recommendationmentioning
confidence: 99%
See 2 more Smart Citations